2013
DOI: 10.1039/c3cc43677b
|View full text |Cite
|
Sign up to set email alerts
|

A robust transparent and anti-fingerprint superhydrophobic film

Abstract: A thin film of polyaniline (PANI) nanofibers on the stainless steels with fluoro-thiol modification was prepared through an optimal polymerization time of aniline using HClO4 as a dopant, showing robust superhydrophobic, transparent and anti-fingerprint properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 27 publications
0
46
0
Order By: Relevance
“…Considering many practical applications, such as clothing, kitchenware, oil pipeline, and so on, antifouling property is of great significance in a wide range of areas . Yuan et al have prepared the superamphiphobic coating with composite ethylene tetrafluoroethylene‐polyaniline functionalized carbon nanotubes.…”
Section: Functional Applicationsmentioning
confidence: 99%
“…Considering many practical applications, such as clothing, kitchenware, oil pipeline, and so on, antifouling property is of great significance in a wide range of areas . Yuan et al have prepared the superamphiphobic coating with composite ethylene tetrafluoroethylene‐polyaniline functionalized carbon nanotubes.…”
Section: Functional Applicationsmentioning
confidence: 99%
“…Despite much effort to date to address this problem, no effective, durable solution to achieve an anti-fingerprint or easy-to-clean coating has been realised. 1 The term easy-to-clean embodies both a decreased uptake of contamination on initial touch as well as the ease this contamination can be removed with, also called cleanability. 2 To address it, the focus has been mainly on creating functional surfaces via thin film coatings in order to decrease the initial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…2 To address it, the focus has been mainly on creating functional surfaces via thin film coatings in order to decrease the initial adhesion. 1,[3][4][5] However, in practice, the adhesion of contamination onto the surface can never be fully prevented due to the very low surface energy of the compounds that make up a fingerprint. 6-8 Achieving superior cleanability behavior is therefore a key performance criterion in practical applications of designing surfaces, in addition to minimizing the adherence of contamination upon initial touch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only limited studies on the fabrication of mechanically durable superhydrophobic surfaces have been reported in the literature. Most mechanically stable superhydrophobic surfaces can maintain their superhydrophobicity only under mild conditions, such as sand impingement, tape‐peeling,[11b] water‐impact tests, supersonic treatments,[12a] or slight friction (a few centimeters or dozens of centimeters of abrasion with sandpaper) . Moreover, a host of current procedures either require complex processing and specialized equipment or are difficult to realize industrial‐scale applications.…”
mentioning
confidence: 99%